MENINGKATKAN KREATIVITAS PESERTA DIDIK PADA PELAJARAN SOSIOLOGI MENGGUNAKAN METODE PEMBERIAN TUGAS - Irmalina Lubis (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
AbstractThis study aims to determine the increase in the creativity of students in the subject matter Sociology Social Interaction using the method of assignment in class X - 6 SMA Negeri 11 Medan Academic Year 2012/2013. With the kretivitas students in learning so that the goal of learning can be achieved by optimally. Classroom action research was conducted at SMAN 11 Terrain. Subjects in this study were students of class X-6, amounting to 38 students, the object of this research is a method pemberin task, and the data collected using observation sheets and questionnaires. In the first cycle there are 7 people or students (18.4%) who received either criterion value with on average 65.2%. In the second cycle increased to 27 or (71%) in the criteria of both creativity and average - average value obtained 83.8%. At the end of the meeting questionnaire contained 5 students (13.1%) who received low learning outcomes and only 27 students (71.1%) who received both learning outcomes and the average value obtained 82.1%. Based on the results from the first cycle and second cycle has been proven empirically significant increase. Thus the use of the method of administration tasks can enhance students' creativity in the eyes of Sociology lesson in class X - 6 SMA Negeri 11 Medan. Keywords: Delivery of Tasks, Social Interaction, Creativity